Complicated symptomatology and diagnosis of Creuzfeld-Jakob disease on a basis of clinical case - Jurga, Marta; Kuśmierczyk, Katarzyna; Karkos, Patrycja; Gruszczyńska, Hanna; Kuderska, Natalia; Jurga, Kacper; Okowińska, Ewa; Cieślik, Aleksandra; Wojtyła, Klaudia; Lambrinow, Jakub (Quality in Sport, 2024)
Creutzfeldt-Jakob disease (CJD) is a rare condition. In this study we describe the diagnosis of the disease in a 73-year old female, presenting dementia. Diagnostic tests unveiled characteristic features of CJD. The diagnosis of CJD was confirmed. It is important to always take into consideration the diagnosis of CJD in the diagnostic process of dementia. Purpose: The aim of this scientific paper is to present symptoms and diagnostic methods of Creutzfeldt-Jakob disease on the basis of a clinical case. Review Methods: We conducted our study as a literature review based on information gathered from PubMed, Embase, GoogleScholar using combinations of the following. As a part of study, we also present a case description from our materials from clinical practice.